CUSTOMER SATISFACTION ON ONLINE SHOPPING AMONG UNIVERSITY STUDENTS DURING PANDEMIC CRISIS OF COVID-19 AT UITM KEDAH - Muhammad Izzuddin bin Abd Azis; Nor Hazira binti Mohamad Hasri; Nurulaini Zamhury (International Journal of Accounting, Finance and Business, 2023)
The satisfaction of customers in online shopping is largely influenced by the quality of delivery services provided. A study by Yingxia Cao et al. (2018) found that delivery services had a significant impact on customer satisfaction in China and Taiwan, while return services and customer services had different effects due to different return policies in each country. In Serbia, a study by Nebojša Vasić et al. (2019) showed that fast, accurate, and reliable shipping was the most critical determinant of customer satisfaction, and customers were willing to pay for delivery services that fulfilled these criteria. During holiday seasons in China, delivery services were identified as a significant factor in online shopping satisfaction, and online retailers' continued improvement of delivery services helped maintain customer satisfaction, according to Shian-Yang et al. (2021). The study by Christina Milioti et al. (2020) revealed that home delivery was the most preferred delivery method for e-groceries in Greece and the UK, followed by pick-up from lockers and stores, with willingness to pay being a significant factor. Meanwhile, Fadilah Siali et al. (2018) found that assurance and reliability were essential factors in determining customer satisfaction with parcel delivery services in Malaysia. Finally, Siqi Ma's study (2017) found that fast and free delivery services increased satisfaction and purchase intentions, with uncertainty mediating the relationship between shipping options and satisfaction.